‘Peace and Security’ (1 Thess 5.3): Prophetic Warning or Political Propaganda? - Weima, Jeffrey A. D. (New Testament studies, 2012)
The phrase ‘Peace and security’ in 1 Thess 5.3 has traditionally been understood as an echo of the OT prophetic warnings (Jer 6.14; Ezek 13.10; Mic 3.5) against false claims of peace. Stronger evidence exists, however, that the apostle is making use of a popular theme of the imperial Roman propaganda machine. The Romans vigorously promoted themselves through various public media as those who provided not only ‘peace’ but also ‘security’, thereby providing a closer parallel to Paul's statement in 5.3 than any OT text. This essay reviews four kinds of evidence—numismatic, monumental, inscriptional and literary—in order to demonstrate in a decisive fashion that the phrase ‘peace and security’ involves an allusion not to prophetic warning but to Roman political propaganda.